The Role of Marketing in Shaping Product and Service Offerings in the Hotel Industry - Yusuf, Oluwatoyin ldowu Susan; Omotoba, Nathaniel Ileri; Olabinjo, Muhammed Adewale (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2024)
This study examines the role of marketing on product-service determination in the hotel industry. Marketing hotel products requires determining the unique selling points of the hotel products so that a hotel operator may know what to promote to attract more guests. The study aims to analyse different marketing techniques used in determining hotel products and services. This study uses a cross-sectional and quantitative approach to achieve its objectives. Thus, data was collected and analysed using quantitative data and Regression Models respectively. Findings reveal that outdoor signs and multiple-story banners as an advertising technique have less significant effect on product-service determination; it is also evident that website advertising and social networking have a significant effect on product-service determination. Based on findings, researchers recommend that hotel operators should ensure that they employ effective marketing techniques to increase the number of patrons to generate more profits for their hotels. In all, hotel operators should embrace website advertising and social networking by encouraging the use of social channels in determining hotel products/services in Nigeria.